Perspectives on the social impacts of second homes in rural South Africa - Hay, Emerentia Antoinette (University of the Free State, 2014)
Second homes as phenomenon in Human Geography has been researched in some detail in developed countries, but considerably little research has been presented on this phenomenon in the developing world. The existing research focuses mainly on economic issues related to second home development – but this research was specifically undertaken better to understand the social perspectives and resultant impacts of this phenomenon on rural communities. Economic issues also came into play, but the main focus was to unravel the social intricacies that second homes bring to a rural environment. Rosendal in the Eastern Free State of South Africa was used as a case study and included the predominantly white town of Rosendal, the black township of Mautse and the surrounding farming community. The area is known as a retreat for city dwellers from the Gauteng region and the capital of the Free State province, namely Bloemfontein. The literature review revealed that social and economic impacts of second home development on host communities, worldwide and locally, play an important role and contribute to the shift of communities from a productivist to post-productivst countryside. Furthermore, social change serves to undermine the social utility of traditional farming – resulting in a differentiated or post-productivist countryside of which second home development is an example. A mixed methods approach within the interpretivist paradigm was utilised for this thesis, where a combination of both qualitative and quantitative research was implemented. Furthermore, a case study approach was used because the study wanted to provide a platform and agenda for future studies on social impacts of second homes. Case studies within the interpretivist paradigm have received relatively little attention from social scientists, especially geographers – therefore it may be argued that this is new territory for second home research in South Africa. The findings revealed that research in South Africa on people with lower incomes as second home owners is almost completely absent. One of the main contributions of this study therefore, is the unraveling of the socio-economic profiles of lower income earners who have second homes, and do not necessarily come from cities. Secondly, research on high amenity rural places often focuses on the potential v impacts of rapid growth in tourism and second home ownership on the ‘host’ community. Part of this worldwide research is the seasonal and weekend resident attachment to such a landscape, but for the current study farm dwellers’ migration was also researched – dwellers who travel during month-ends to town locations or ‘informal dwellings’, which may lead to the erosion of (or in constructive terms rather change in) the existing socio-cultural fabric, as rural values are mixed with the urban (and farm) values of incomers. Thirdly it was found that the six indicators of a post-productivist countryside of Wilson and Rigg (2003) can only be partially applied to the current case study. This indicates that developing countries are probably moving partially to a post-productivist state in the rural areas, but that certain factors not known to developed countries are also at work and contribute to permutations of the mentioned indicators. The thesis closes with a suggestion that post-productivist theory may have to be reviewed for developing country environments.

Tweede huise as ‘n verskynsel in Menslike Geografie is reeds deeglik nagevors in ontwikkelde lande, maar betreklik min navorsing oor hierdie fenomeen bestaan in ontwikkelende lande. Die bestaande navorsing fokus hoofsaaklik op ekonomiese kwessies betreffende tweede huis-ontwikkeling – maar hierdie studie fokus spesifiek op die sosiale perspektiewe en gevolglike impakte van hierdie verskynsel op plattelandse gemeenskappe. Ekonomiese kwessies word ook aangespreek, maar die hooffokus is om die sosiale impakte van tweede huiseienaarskap op plattelandse omgewings te ondersoek. Rosendal in die Oos-Vrystaat van Suid-Afrika is benut as gevallestudie en sluit die hoofsaaklik wit dorp van Rosendal, die swart dorp Mautse en omliggende boedery- gemeenskap in. Die gebied is bekend en veral gewild onder stedelinge vanaf Gauteng en die hoofstad van die Vrystaat, naamlik Bloemfontein. Die literatuurstudie toon dat sosiale en ekonomiese impakte van tweede huis- ontwikkeling op gemeenskappe – wêreldwyd en plaaslik – ’n beduidende rol speel en bydra tot die beweging vanaf ’n produktiewe na ’n post-produktiewe gemeenskap. Verder ondermyn sosiale verandering die sosiale bruikbaarheid van tradisionele boerdery – en gevolglik lei dit tot ’n gedifferensieerde of post-produktiwistiese gemeenskap met tweede huis-ontwikkeling as kenmerk. ’n Gemengde metode-benadering binne die interpretivistiese paradigma is gebruik in die ondersoek, waarna ’n kombinasie van beide kwalitatiewe en kwantitatiewe navorsing geïmplementeer is. ’n Gevallestudie-metode is gebruik met die oog op die skep van ’n platform vir toekomstige navorsing oor sosiale impakte van tweede huiseienaarskap. Min navorsing deur sosiale wetenskaplikes (veral geograwe) is nog opgelewer oor gevallestudies binne die interpretivistiese paradigma – daarom kan geargumenteer word dat dit nuwe terrein is vir tweede huis-navorsing in Suid-Afrika. Uit die bevindings is dit duidelik dat navorsing gerig op tweede huiseienaars met laer inkomstes in Suid-Afrika feitlik onbekend is. Een van die primêre bydraes van hierdie studie is die ontleding van die sosio-ekonomiese profiele van laer inkomste-verdieners as tweede huiseienaars wat nie noodwendig van stede af kom nie. Tweedens, navorsing oor gewilde plattelandse plekke fokus gewoonlik op die potensiële impakte van die geweldige groei in toerisme en tweede huiseienaarskap op die plaaslike gemeenskap. Deel van hierdie wêreldwye navorsing is die seisoenale en naweek inwonergehegtheid aan so ’n gemeenskap, maar die huidige studie het ook gefokus op plaaswerker-migrasie – waar hul dan gewoonlik gedurende maandeinde na die dorp reis na hul informele struktuur. Hierdie tendense kan lei tot die erodering van die bestaande sosio-kulturele samestelling, want die plattelandse waardes meng met plaas- en stedelike waardes. Derdens is bevind dat die ses indikatore van ’n post-produktivistiese gemeenskap van Wilson en Rigg (2003), slegs gedeeltelik toegepas kan word op die huidige gevallestudie. Dit lyk asof ontwikkelende lande hoogstens gedeeltelik beweeg na ’n post-produktivistiese toestand in veral plattelandse gemeenskappe, maar dat sekere faktore, onbekend aan ontwikkelde lande, ook aan die werk is om by te dra tot permutasies van die genoemde indikatore. Die proefskrif sluit af deur voor te stel dat die post-produktivistiese teorie hersien moet word om meer toepaslike voorsiening te maak vir ontwikkelende plattelandse omgewings.
Thesis (Ph.D. (Geography))--University of the Free State, 2014
Keywords: Human geography South Africa; Second homes South Africa; Rural development South Africa; Interpretivism; Post-productivism; Post-productivist countrysides; Developing world; Social and economic impacts; Rurality; Low income second home owners; Escapism; Family pull factor